2018
DOI: 10.1111/1471-0528.15456
|View full text |Cite
|
Sign up to set email alerts
|

Childhood growth of singletons conceived following in vitro fertilisation or intracytoplasmic sperm injection: a systematic review and meta‐analysis

Abstract: Children born following IVF/ICSI do not have impaired long-term weight or height compared with spontaneously conceived children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 35 publications
2
26
0
Order By: Relevance
“…There remains a paucity of studies examining patterns of childhood growth in children conceived with ICSI. In a recent systematic review and meta-analysis of studies of childhood growth in singletons (age range 1-28 years, median 5 years), children conceived with ICSI were found to have similar weight and height to those conceived spontaneously (17). In several of the included studies, comparable childhood weight was observed in the ICSI and spontaneous conception groups, despite ICSI children having lower birth weights, indicating a higher rate of postnatal growth in this group.…”
Section: Growth Adiposity and Cardiometabolic Healthmentioning
confidence: 98%
See 1 more Smart Citation
“…There remains a paucity of studies examining patterns of childhood growth in children conceived with ICSI. In a recent systematic review and meta-analysis of studies of childhood growth in singletons (age range 1-28 years, median 5 years), children conceived with ICSI were found to have similar weight and height to those conceived spontaneously (17). In several of the included studies, comparable childhood weight was observed in the ICSI and spontaneous conception groups, despite ICSI children having lower birth weights, indicating a higher rate of postnatal growth in this group.…”
Section: Growth Adiposity and Cardiometabolic Healthmentioning
confidence: 98%
“…Several reviews of the literature pertaining to long-term health and developmental outcomes of children conceived with ICSI have now been undertaken (14)(15)(16)(17). These reviews identify possible increased risks of certain neurodevelopmental disorders, as well as impaired cardiometabolic and reproductive health profiles among children conceived with ICSI.…”
mentioning
confidence: 99%
“…By contrast, a meta‐analysis of 11 studies 5 and two large cohort studies 6,7 found a reduced risk of SGA and FGR by about 45% and an increased risk of being large‐for‐gestational age (LGA) by 30–90%, in IVF/ICSI pregnancies conceived after FBT, as compared to after fresh embryo transfer. No long‐term weight and height differences were found above 5 years of age in a large meta‐analysis of 20 studies investigating childhood growth of singletons conceived after IVF/ICSI 8 . The basis for reduced fetal growth in IVF/ICSI pregnancies from fresh cycles and greater fetal growth following FBT remains to be determined; however, it is clear that fetal and placental development in these different settings need further investigation.…”
Section: Introductionmentioning
confidence: 97%
“…Another recent meta-analysis indicated that children conceived by IVF and ICSI showed a lower weight during the first 4 years of age, with the difference disappearing afterwards (Bay et al 2019), indicating an enhanced growth velocity during early development. Rapid growth during early childhood can increase the risk of developing obesity and hypertension later in life (Mihrshahi et al 2011, Lei et al 2015.…”
Section: Assisted Reproductive Technologiesmentioning
confidence: 99%